Solid-phase microextraction using a β-ketoenamine-linked covalent organic framework coating for efficient enrichment of synthetic musks in water samples. Issue 19 (5th May 2020) - Wen, Lian; Wu, Peng; Wang, Lei-Lei; Chen, Li-Zong; Wang, Ming-Lin; Wang, Xia; Lin, Jin-Ming; Zhao, Ru-Song
Abstract : This study indicated the promising applicability of the TpPa-1 as a solid-phase microextraction fiber coating for reliably detecting synthetic musks at trace levels from environmental samples. Abstract : Covalent organic frameworks with tunable porous crystallinity and outstanding stability have recently exhibited fascinating pretreatment performance as solid-phase microextraction coatings. In this report, a β-ketoenamine-linked covalent organic framework (TpPa-1) was successfully constructed through a Schiff-base-type reaction between 1, 3, 5-triformylphloroglucinol (Tp) and para -phenylenediamine (Pa-1). A TpPa-1 coating was then fabricated on a stainless-steel fiber for capturing trace synthetic musks. This TpPa-1 coating exhibited strong interaction with synthetic musks because of its hydrophobicity and π–π affinity. This TpPa-1-based solid-phase microextraction methodology, coupled with gas chromatography-tandem mass spectrometry, provided high enrichment factors (1214–12 487), wide linearity (0.5–1000 ng L −1 ), low limits of detection (0.04–0.31 ng L −1 ), and acceptable reproducibility (relative standard deviation, <10%) for nine synthetic musks. Recoveries at three spiked levels in three types of water samples were between 76.2% and 118.7%. These results indicated the promising applicability of the TpPa-1 as a solid-phase microextraction fiber coating for reliably detecting trace concentrations of synthetic musks in the environment.